Studenckie Koło Naukowe „Wentylator” – charakterystyka działalności - Królak, Patrycja; Koralewska, Kamila (Lodz University of Technology. Faculty of Civil Engineering, Architecture and Environmental Engineering, 2019)
Artykuł opisuje historię i działalność w roku akademickim 2017/2018 Studenckiego Koła Naukowego „Wentylator”. Zawiera również opis ewolucji loga/symbolu koła. Opisuje dokładną historię Dni Inżynierii Środowiska, relację wraz z fotografiami z ostatniego konkursu „Go Balance – nie daj się wyprowadzić z równowagi” oraz dnia otwartego dla szkół podstawowych.

The article describes the history and activity in the academic year 2017/2018 of the Student Scientific Club „Wentylator”. It also contains a description of the science club’s logo. It describes the exact history of Environmental Engineering Days, a reports and the photographs from the las competition "Go Balance – do not get out of balance" and an open day for primary schools.